Integrin β6 deficiency protects mice from experimental colitis and colitis-associated carcinoma by altering macrophage polarization - Sun, Qi; Lu, Zhihua; Ma, Lei; Xue, Dong; Liu, Chang; Ye, Changchun; Huang, Wenbo; Dang, Yueyan; Li, Fanni (Frontiers in Oncology, 2023)
Background Given the key role of integrins in maintaining intestinal homeostasis, anti-integrin biologics in inflammatory bowel disease (IBD) are being investigated in full swing. However, the unsatisfactory efficacy and safety of current anti-integrin biologics in clinical trials limit their widespread use in clinic. Therefore, it is particularly important to find a target that is highly and specifically expressed in the intestinal epithelium of patients with IBD. Methods The function of integrin αvβ6 in IBD and colitis-associated carcinoma (CAC) with the underlying mechanisms has been less studied. In the present study, we detected the level of integrin β6 within inflammation including colitis tissues in human and mouse. To investigate the role of integrin β6 in IBD and CAC, integrin β6 deficient mice were hence generated based on the construction of colitis and CAC model. Results We noted that integrin β6 was significantly upregulated in inflammatory epithelium of patients with IBD. Integrin β6 deletion not only reduced infiltration of pro-inflammatory cytokines, but also attenuated disruption of tight junctions between colonic epithelial cells. Meanwhile, lack of integrin β6 affected macrophage infiltration in mice with colitis. This study further revealed that lack of integrin β6 could inhibit tumorigenesis and tumor progression in CAC model by influencing macrophage polarization, which was also involved in attenuating the degree of intestinal symptoms and inflammatory responses in mice suffering from colitis. Conclusions The present research provides a potentially new perspective and option for the treatment of IBD and CAC.